2013
DOI: 10.3389/fnhum.2013.00236
|View full text |Cite
|
Sign up to set email alerts
|

Social behavior in the “Age of Empathy”?—A social scientist's perspective on current trends in the behavioral sciences

Abstract: Recently, several behavioral sciences became increasingly interested in investigating biological and evolutionary foundations of (human) social behavior. In this light, prosocial behavior is seen as a core element of human nature. A central role within this perspective plays the “social brain” that is not only able to communicate with the environment but rather to interact directly with other brains via neuronal mind reading capacities such as empathy. From the perspective of a sociologist, this paper investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this sense, we are trying to work through strategies through which more compelling accounts of the environment, of society, of culture, of milieu (to use the technical term of Goldstein 1995Goldstein [1934) might yet get pulled through laboratorybased neurobiological studies. Because, as Svenja Matusall also reminds us, we can trace rather different accounts of the 'social' even within the relatively small world of social neuroscience -which is to say, this field is itself contested in various ways (Matusall 2013). The tension between the rather open account of the 'social' that appears in Cacioppo and Berntson, and the thinner, more vitiated descendant of that account that we read in much subsequent psychological work is sobering.…”
Section: Accounting For the Socialmentioning
confidence: 95%
“…In this sense, we are trying to work through strategies through which more compelling accounts of the environment, of society, of culture, of milieu (to use the technical term of Goldstein 1995Goldstein [1934) might yet get pulled through laboratorybased neurobiological studies. Because, as Svenja Matusall also reminds us, we can trace rather different accounts of the 'social' even within the relatively small world of social neuroscience -which is to say, this field is itself contested in various ways (Matusall 2013). The tension between the rather open account of the 'social' that appears in Cacioppo and Berntson, and the thinner, more vitiated descendant of that account that we read in much subsequent psychological work is sobering.…”
Section: Accounting For the Socialmentioning
confidence: 95%
“…Nevertheless, researchers such as Niko Tinbergen (Bateson and Laland, 2013 ) have applied this framework to inform elements of social cognition at multiple evolutionary levels, probing the relationships among observable behaviors and determining whether they emerge at analogous stages of brain development, have phylogenetic continuity and serve homologous adaptive functions between species. As a result, the key neural mechanisms underlying social behavior in animal models have become grounded in the fields of biology and biomedicine (Cacioppo and Decety, 2011 ; Matusall, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…And as recent studies have shown, parenting-associated prosocial helping behaviors not only enhance the survival of the offspring, but also promotes better health, slower decline in functioning levels and lower risk of mortality for care-givers ( Brown and Brown, 2015 ). Collectively, the evidence indicating prosocial altruistic capability provides for complex interactions that have come to form the foundation of our civil, societal interactions ( Matusall, 2013 ). Social interactions often extend not only to members of our families, but to other members of our own social species, and often to members of other domesticated species on which we depend for our survival and social well-being.…”
Section: Evolution Of the Prosocial Brainmentioning
confidence: 99%